English Studentsâ€™ Self Instruction Strategy in Following Microteaching Class - Eki Saputra; Putri Kurnia Ilahi; Fetriani Fetriani (Teaching English and Language Learning English Journal, 2021)
This research was aimed to investigate the strategy of self instruction which is applied by English students as pre-service teacher in following microteaching. The researcher used a descriptive quantitative data to obtain the data about self instruction implemented by students in following microteaching class. The population of this research was 6th semester of English students who enrolled Microteaching class at the English Education Program of Muhammadiyah University of Bengkulu Academic Year 2020/2021. There were 46 students who become the population of this research. The researcher used a questionnaire and observation checklist as the instrument of this research. The finding showed that there were five strategies of self instruction namely; cognitive modelling stage, overt external guidance, overt self guidance, faded overt self guidance, and covert self instruction. Moreover, the dominant role of lecturer was Overt External Guidance.Â Keywords: Self Instruction Strategy, Microteaching Class